Internet of Things (IoT) Sistem Monitoring Suhu, Kelembapan dan Insensitas Cahaya Pada Ruang Penyimpanan Obat - Novalin Koru; Abdul Zaid Patiran; Lorna Yertas Baisa (LPPM STIKOM Tunas Bangsa, 2024)
Medicine storage space is a crucial element in the healthcare industry. The safety and quality of medications heavily rely on the appropriate temperature and humidity conditions. Uncontrolled temperature fluctuations or inadequate humidity levels can lead to the loss of effectiveness of medications or even pose risks to patients. This research aims to monitor temperature, humidity, and light intensity at Nabila Farma pharmacy in real-time using hardware devices such as ESP8266 and sensors like DHT11, BH1750. The collected data will be sent to Google Sheets for easy access and monitoring. This presents a practical solution to maintain the quality and safety of drugs by ensuring optimal storage conditions